The electronic notarial document - Llopis Benlloch, José Carmelo (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The concept of electronic notarial document was introduced into the Spanish legal system by the Act 24/2001, of December 27. This legislation/ established the requirements and the essence of such a document without creating a new subtype of notarial document, but simply allowing and regulating its transfer to electronic media. Subsequently, the Reglamento Notarial was amended in 2007 to adapt it to the said Act, while the Notaries began to work on modernizing its technological infrastructure to allow the implementation of a true notarial electronic office.
Keywords: electronic notarial document; notarial electronic office